2022
DOI: 10.3390/d14080612
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ethnobotanical Indices in the Utilization of Five Medicinal Herbaceous Plant Species in Benin, West Africa

Abstract: The ethnobotanical utilization of five neglected herbaceous species, Argemone mexicana L., Heliotropium indicum L., Kedrostis foetidissima (Jacq.) Cogn., Peperomia pellucida (L.) Kunth and Schrankia leptocarpa DC. was investigated in Southern Benin to determine the ethnomedicinal and magic knowledge on them. Thirty-six herbal medicine traders were surveyed in six different markets in three districts. Four ethnobotanical indices were used. All informants traded A. mexicana and the majority traded H. indicum, K.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…However, for Foeniculum vulgare , Ficus carica , Malva sylvestris , Urtica dioica , Crataegus monogyna , Fragaria vesca , Juglans regia , Taraxacum officinale , Quercus ilex, and Rorippa nasturtium-aquaticum , our cultural index is much higher than if we compare it with other investigations carried out in the Iberian Peninsula [ 44 , 45 ]. Thus, the use of quantitative and qualitative ethnobotanical indices is relevant for the development of ethnobotany-related studies [ 46 ]. It draws attention to Urtica urens that is consumed in traditional spring plates in Italy, Belarus, Greece, and other Mediterranean countries, while, in Bulgaria, it is not common as a food plant, and only Urtica dioica is employed on a large scale, and the cultivated one has been sold in local markets recently [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, for Foeniculum vulgare , Ficus carica , Malva sylvestris , Urtica dioica , Crataegus monogyna , Fragaria vesca , Juglans regia , Taraxacum officinale , Quercus ilex, and Rorippa nasturtium-aquaticum , our cultural index is much higher than if we compare it with other investigations carried out in the Iberian Peninsula [ 44 , 45 ]. Thus, the use of quantitative and qualitative ethnobotanical indices is relevant for the development of ethnobotany-related studies [ 46 ]. It draws attention to Urtica urens that is consumed in traditional spring plates in Italy, Belarus, Greece, and other Mediterranean countries, while, in Bulgaria, it is not common as a food plant, and only Urtica dioica is employed on a large scale, and the cultivated one has been sold in local markets recently [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…About 80% of the world's population still relies on traditional plant-based medicines for primary health care because of their effectiveness, some may have side effects, and easily accessible at affordable prices (Ullah et al 2018). Different ethnic groups throughout the world have a very close affinity with plants both for their personal use and commercial purposes (Dossou-Yovo et al 2021, Dossou-Yovo et al 2022. Since immemorial time, it was reported that humans depends on the plants for different life activities and services (Harshberger 1896).…”
Section: Introductionmentioning
confidence: 99%
“…In its current state, the population of Abomey-Calavi district is constantly growing as a result of the urbanisation created by the city of Cotonou on the western coast of Benin [12]. With an intercensal growth rate of 6.93% between 2002 and 2013, the municipality of Abomey-Calavi has a demographic weight of 46.9% in the Atlantique department [13], and is one of the most densely populated towns in Benin [14]. Despite this demographic feature and the existence of an urbanisation plan, this area has only four public green spaces, with a surface area of approximately 8.08 ha, representing 0.015% of the district's surface area, for a ratio of 0.06 m 2 of green space per inhabitant [15].…”
Section: Introductionmentioning
confidence: 99%